Acute badminton injuries - Fahlstrom, M.; Bjornstig, U.; Lorentzon, R. (Scandinavian Journal of Medicine & Science in Sports, 1998)
During 1990-1994, 1.2% of all sports injuries that required emergency care at the University Hospital of Umea were caused by badminton. In 90.7% of the cases the patients described themselves as recreational players or beginners. There were 51.3% minor injuries (AIS 1) and 48.7% moderate injuries (AIS 2). The lower extremities were affected in 92.3% of the cases. Achilles tendon ruptures (34.6%) and ankle sprains and fractures (29.5%) were the most frequent. By the time of the follow-up (10-69 months), 52.6% of the players still had symptoms from the injuries and 39.5% had not been able to return to playing badminton. Our data indicate the importance of adequate treatment and rehabilitation after acute badminton injuries.